ANALYSIS OF WHATSAPP BASED ONLINE SERVICES EFFECTIVITY AT KMU MADURA EYE CLINIC - Dana Rohmana; Nur Cahyadi (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Service quality is now very important for companies engaged in services. Therefore this study aims to determine the quality of service by using whatsapp-based online registration at the Madura Main Eye Clinic by filling in the available format and carried out 1 day before examining this study using a descriptive qualitative method. The data collection technique used was unstructured in-depth interviews. With the results obtained at the Kmu Madura Eye Clinic that WhatsApp-based online registration which was carried out by filling in the form the previous day greatly affected the quality of service because it could maintain patient satisfaction at the Kmu Madura Eye Clinic and the quality of service at the Kmu Madura Eye Clinic could be said to be good and very effective.